X-Ray powder diffraction. The practical application of the method in the pharmaceutical expertise - V. S. Kuzmin; V. V. Chernyshev; V. A. Yashkir; V. A. Merkulov (Регуляторные исследования и экспертиза лекарственных средств)
Method of X-ray phase analysis based on obtaining and analyzing the diffraction pattern resulting from the diffraction of x-rays scattered by electrons of the atoms of the irradiated polycrystalline sample. Using this method in the framework of a pre-registration examination the study of pharmaceutical substances temosolomide, form I of valacyclovir hydrochloride monohydrate and quetiapine fumarate (form I) to confirm their authenticity. The results obtained allowed to conclude that the claimant substance temosolomide is not primary, and the substance of valacyclovir does not meet the stated requirements in terms of "Authenticity".